Cultural Messages of the Borobudur Temple's Symbols Seen from Aerial Photography Media - Ade Dani Setiawan (Journal of Visual Art and Design, 2013)
Aerial photography depicts real images and reality requirements of the real images on scientific encoding, presenting objects clearly, accurately, without any manipulations. Accurate consideration and exact flying direction coordinate will capture objects of miles away in minutes for time is too precious too loose in the air. Aerial photography has flexibility. It can move on the physical reality, abstract reality, as well as reality which deliver messages to public. By means of aerial photography Borobudur temple can be seen as a whole to complete the familiar horizontal perspective. Borobudur temple has plenty of geometrical forms on its whole parts, i.e. diagonal lines, curves, upright lines, triangles, horizontal, cones, cubes, squares, and circles. These geometrical forms symbolize Buddhist cultural and spiritual messages. This research attempts to explicate the connections of symbols and messages on the Borobudur, its nature landscape and cultural landscape using vertical approaches as recorded in aerial photography. The explication applies semiotics theory of Roland Barthes, completed with photography theories. This explication aims to enrich the former readings fulfilled from horizontal view, in order to reveal more signs and messages carried by the physical shape of the temple.